1969
DOI: 10.1017/s0021853700009518
|View full text |Cite
|
Sign up to set email alerts
|

French Policy and the Origins of the Scramble for West Africa

Abstract: This paper is a contribution to the current debate about the origins of the scramble for West Africa. It analyses the internal dynamics of French expansion and argues that the crucial change in French African policy occurred not in 1882–3, as commonly assumed, but in 1879–80. The policies adopted at this time, although their roots can be traced back to the governorship of Louis Faidherbe in Senegal, were distinguished by a new willingness on the part of the government in Paris to establish political as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The Frenchman Major Gustave Borgnis‐Desbordes was a classic example. Placed in charge of Upper Senegal in the 1880s, he disobeyed orders, launched daring unauthorized military offensives, and was “virtually impossible to control” (Newbury & Kanya‐Forstner, , p. 266). There were many others of his ilk, ranging from the armistice‐breaking Major‐General George Colley through to Louis Alexandre Brière de L'Isle, the governor of Senegal in 1876.…”
Section: Weak Statementioning
confidence: 99%
See 1 more Smart Citation
“…The Frenchman Major Gustave Borgnis‐Desbordes was a classic example. Placed in charge of Upper Senegal in the 1880s, he disobeyed orders, launched daring unauthorized military offensives, and was “virtually impossible to control” (Newbury & Kanya‐Forstner, , p. 266). There were many others of his ilk, ranging from the armistice‐breaking Major‐General George Colley through to Louis Alexandre Brière de L'Isle, the governor of Senegal in 1876.…”
Section: Weak Statementioning
confidence: 99%
“…There were many others of his ilk, ranging from the armistice‐breaking Major‐General George Colley through to Louis Alexandre Brière de L'Isle, the governor of Senegal in 1876. Brière “demonstrated the metropolitan government's inability to control a determined local subordinate who was astute enough to perceive its weaknesses and bold enough to exploit them” (Newbury & Kanya‐Forstner, , p. 259). Such were the hazards of long‐distance instructions to strong personalities, and such was the modus operandi of states separated from their agents by great distances and often thwarted by alternate agendas and local imperatives.…”
Section: Weak Statementioning
confidence: 99%
“…The difficulty here is that French plans for moving into West Africa were formulated in 1879, three years before the occupation of Egypt, and therefore cannot have been prompted by it. 168 In fact, the French congratulated the British on the action they took in 1882 because it appeared to safeguard rather than to imperil French business and personnel. 169 At that time France was heavily engaged in Tunisia, Algeria, and Indochina, and used Britain's action in Egypt to assist her there rather than in sub-Saharan Africa.…”
Section: Causes Of Actions and Their Consequencesmentioning
confidence: 99%
“…103 On the other hand, the most severe critics of Hobson and Lenin can concede the importance of trade. Some studies have shown as well that perceptions of economic gain-especially in the case of France-can be more relevant to understanding what happened than the realities (Fieldhouse, 1973;Newbury and Kanya-Forstner, 1969;Hynes, 1969). And Ronald Robinson's recasting of arguments about the breakdown of older collaborative mechanisms between Europeans and Africans is compatible with Marxist arguments that stress why European demands escalated in the late nineteenth century (Robinson, 1972;Weiskel, 1980: 239-40).…”
Section: Imperialismmentioning
confidence: 99%